2011
DOI: 10.1002/micr.20905
|View full text |Cite
|
Sign up to set email alerts
|

Vascular complications and microvascular free flap salvage: The role of thrombolytic agents

Abstract: The decreased incidence of fat necrosis may be attributable to dissolution of thrombi in the microvasculature with the administration of thrombolytics. Although the use of adjuvant thrombolytic therapy does not appear to impact the rate of flap salvage, their use may have secondary benefits on overall flap outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 29 publications
(41 reference statements)
0
42
0
Order By: Relevance
“…Chang et al used tissue plasminogen activator (tPA), streptokinase and urokinase for vascular complications of free flaps with encouraging results [15]. Low-molecular-weight heparin has been shown to help increase the survival rates of congested skin flaps [16].…”
Section: Discussionmentioning
confidence: 98%
“…Chang et al used tissue plasminogen activator (tPA), streptokinase and urokinase for vascular complications of free flaps with encouraging results [15]. Low-molecular-weight heparin has been shown to help increase the survival rates of congested skin flaps [16].…”
Section: Discussionmentioning
confidence: 98%
“…On analysis of the literature it is clear that is no consensus on the amount of tPA used (Table 1) [8,[10][11][12]. The average amount used was 2.0 mg, but 2.5 mg and 4.0 mg has also been used.…”
Section: Discussionmentioning
confidence: 99%
“…In 1987 Lipton and Jupiter, first reported pharmacological thrombolysis by administering streptokinase intra‐arterially for salvage of an osteocutaneous fibular free flap that suffered from venous pedicle thrombosis. Today, intra‐arterial administration is well‐described and many studies reported successful free flap salvage . Notwithstanding, late or recurrent flap thrombosis can be devastating and flap damage or even loss is common in such cases .…”
Section: Discussionmentioning
confidence: 99%
“…The window for intervention that may allow successful free flap salvage appears to be within the first 24 hours . However in difficult vascular conditions and recurrent cases of venous thrombosis, thrombolytic drugs have been described for salvage in addition to surgical revision, thrombectomy, and irrigation with heparin solution …”
mentioning
confidence: 99%